Narracja autobiograficzna w biegu życia - Dryll, Elżbieta; Cierpka, Anna (Człowiek i Społeczeństwo, 2023)
The aim of the article is to present the concept and research on the development of autobiographical narrative in the course of a person’s life. Reference was made to basic concepts important for the analysis of the topic: the definition of narrative, constructionist assumptions, understanding the process of creating self-narrative and the definition of autobiographical narrative. The considerations also include the issue of autobiographical memory and the discussion on understanding autobiographical narrative as monolithic vs. polyphonic. The following subchapters discuss the predispositions and development of early narrative competences, the beginnings of constructing an autobiographical narrative, the mechanisms of shaping and changing the autobiographical narrative in adulthood, including the characteristic features of self-narratives in late adulthood. The review of research presented in the article documents the mechanisms of shaping the autobiographical narrative, the directions of its changes in the life course and selected relationships important for understanding the process of these changes (e.g. the issue of increasing the ability to reflect biographically with age, fulfilling the need for generativity, the effect of intentionally minimizing unpleasant feelings in senior age, the concept of gerotranscendence, etc.). The article ends with reflections on the importance of constructing an autobiographical narrative in the modern world, the availability of autobiographical reflection and its meaning-creating value.